Defensive interactions in soccer small-sided games: an integrated approach between the fundamental tactical principles and the social network analysis - Gibson Moreira Praça; Raphael Brito e Sousa; Sarah da Glória Teles Bredt; Filipe Manuel Clemente; Israel Teoldo; Henrique de Oliveira Castro; Gustavo De Conti Teixeira Costa; Pedro Emílio Drumond Moreira (Universidade Federal de Santa Catarina, 2018)
This study aimed to 1) present a new analysis of the interactions between the tactical principles of defensive coverage and delay using the Social Network Analysis (SNA); 2) compare the defensive cooperation patterns presented by players of different categories during a 3vs.3 soccer small-sided games SSG; 3) compare the level of defensive prominence presented by defenders, midfielders, and forwards in 3vs.3 SSG within and between different categories. Twenty-eight soccer athletes from U-13 (n=14) and U-14 (n=14) categories of a sports club performed 3vs.3 SSG for the analysis of the defensive tactical principles. Defensive interactions were considered successful defensive coverage and a delay actions performed within the same time interval. Macro (density and clustering coefficient) and micro (degree centrality, degree prestige and page rank) analyses were used as SNA measures. Results indicated no significant differences between categories for the macro and micro analyses. Only in the U-14 category, midfielders presented higher prominence levels than the other playing positions (p=0.004). We concluded that U-13 and U-14 athletes are not different regarding defensive cooperation patterns. A higher positional tactical knowledge obtained through deliberate practice is essential to induce different defensive interactions between playing positions, as shown by significant differences only in the U-14 category.